Power Control and Voltage Regulation for Grid-Forming Inverters in Distribution Networks - Xichao Zhou; Zhenlan Dou; Chunyan Zhang; Guangyu Song; Xinghua Liu (Machines, 2025)
This paper proposes a robust voltage control strategy for grid-forming (GFM) inverters in distribution networks to achieve power support and voltage optimization. Specifically, the GFM control approach primarily consists of a power synchronization loop, a voltage feedforward loop, and a current control loop. A voltage feedforward control circuit is presented to achieve error-free tracking of voltage amplitude and phase. In particular, the current gain is designed to replace voltage feedback for improving the current response and simplifying the control structure. Additionally, in order to optimize voltage and improve the power quality at the terminal of the distribution network, an optimization model for distribution transformers is established with the goal of the maximum qualified rate of the load-side voltage and minimum switching times of transformer tap changers. An enhanced whale optimization algorithm (EWOA) is designed to complete the algorithm solution, thereby achieving the optimal system configuration, where an improved attenuation factor and position updating mechanism is proposed to enhance the EWOA’s global optimization capability. The simulation results demonstrate the validity and feasibility of the proposed strategy.